The Origin and Diversification of the Hyperdiverse Flora in the Chocó Biogeographic Region - Pérez-Escobar, Oscar Alejandro; Lucas, Eve; Jaramillo, Carlos; Monro, Alexandre; Morris, Sarah K.; Bogarín, Diego; Greer, Deborah; Dodsworth, Steven; Aguilar-Cano, José; Sanchez Meseguer, Andrea; Antonelli, Alexandre (Frontiers in Plant Science, 2019)
Extremely high levels of plant diversity in the American tropics are derived from multiple interactions between biotic and abiotic factors. Studies have focused on macro-evolutionary dynamics of the Tropical Andes, Amazonia and Brazil’s Cerrado and Atlantic forests during the last decade. Yet, other equally important Neotropical biodiversity hotspots have been severely neglected. This is particularly true for the Chocó region on the north-western coast of South and Central America. This geologically complex region is Earth’s fifth most biodiverse hotspot, hosting approximately 3% of the global plant species. Here, we test Gentry’s [1982a] proposal of a northern Andean-Central American Pleistocene origin of the Chocoan flora using phylogenetic reconstructions of representative orchid lineages in the American tropics. We show that orchids in the Chocó are derived mostly from Andean migrants. Contributions from distant biogeographical areas also exist but are fewer. We also identify a strong floristic connection between the Chocó and Central America, revealed by multiple migrations towards the Chocó during the last 5 million years. The dated phylogenetic reconstructions suggest a Pleistocene onset of the Chocó flora. Taken together, results support Gentry’s assumption of a Pleistocene origin, compound assembly of the Chocoan biodiversity hotspot. Strong Central American-Chocoan floristic affinity may be partly explained by the accretion to north-western South America of a land mass derived from the Caribbean plate. Additional densely sampled phylogenies of prominent Chocoan lineages also well represented across the Neotropics could enlighten the role of land mass migrations through time in the assembly of floras in biodiversity hotspots.